Mempertahankan Citra dan Reputasi dalam Krisis: Studi Kasus PT Kimia Farma Tbk - Sandova, Ibnu; Karen, Nashuha Syaidelfi; Putri, Wahyuni Dwi; Yudistia, Nadia; Havifi, Ilham (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
Corporate image and reputation are heavily influenced by public perception of credibility and quality. The 2021 crisis involving PT Kimia Farma’s use of reused rapid test kits at Kualanamu Airport highlights the importance of crisis management. This research uses a qualitative approach to analyze the company's communication strategies in addressing the crisis. The findings show that quick response, transparency, and restoring public trust through effective communication are crucial for repairing corporate image and reputation. The study emphasizes the importance of structured crisis strategies in maintaining consumer trust, especially in the healthcare sector